Faktor-Faktor yang Mempengaruhi Harga Saham - Rizqi Prima Hanifa Alethea; Sufiyati Sufiyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Stock price is one of the indicators commonly used by investors to assess a company's condition and future prospects. Changes in stock prices may be influenced by various factors originating from both internal and external conditions of the company. This study examines the effect of dividend policy and capital structure on stock prices of consumer non-cyclical companies in the food & beverages subsector listed on the Indonesia Stock Exchange during 2022–2024. Secondary data obtained from annual reports and financial statements were used in this study. The research sample was selected using a purposive sampling method and obtained 84 company sample data. Data were analyzed using panel data regression with the assistance of EViews 13 software. The results of the study indicate that dividend policy has a partial and significant negative effect on stock prices, while capital structure has no effect. This finding indicates that the lower the dividends distributed by a company, the greater investor interest in investing in that company.